Predicting cooperation in competitive conditions: The role of sportspersonship, moral competence, and emotional intelligence. (July 2017) - Perry, John L.; Clough, Peter J.
Abstract: Objectives: The purpose of the present study was to examine the predictive capabilities of sportspersonship, moral competence, and emotional intelligence on cooperation in varying competitive conditions. Design: An experimental study was conducted, examining responses in a prisoner's dilemma game with manipulated conditions. Method: Forty-three participants were randomly assigned to an accumulative or competitive condition, in which they contested 10 rounds of choosing to cooperate or defect. Results: Whether the condition was accumulative or competitive did not significantly predict cooperation. In the final round of each contest however, cooperation was significantly reduced. Sportspersonship predicted a significant amount of cooperation percentage, while final round cooperation was predicted by emotional intelligence. Conclusions: Cooperation is in part determined by individual levels of sportspersonship in all conditions except when actions are free of future consequence. In such conditions, emotional intelligence appears to be a stronger indicator of cooperation. The implications of the study are that researchers and practitioners should consider how to develop sportspersonship and emotional intelligence to boost cooperation in various domains. Highlights: Sportspersonship significantly predicts cooperation in prisoner's dilemma game. Sportspersonship fails as predictor of cooperation in extremely competitive conditions. Emotionality intelligence predicts cooperation in highly competitive conditions only.